AN INFLUENCE OF PARTICIPATIVE LEADERSHIP, ORGANIZATIONAL CULTURE, AND TRAINING ON EMPLOYEE PERFORMANCE WITH EMPLOYEE JOB SATISFACTION AS A MODERATING VARIABLE - Nita Aprilia; Elwisam Elwisam (Jurnal Apresiasi Ekonomi, 2024)
Employee performance in the last 3 years has fluctuated so there must be a solution to deal with this. This study aims to further analyze Participative Leadership, Organizational Culture, and Training on Employee Performance with Employee Job Satisfaction as a moderating variable. The sample in this study used the Slovin method and obtained a sample size of 100. From the results of the hypothesis test, it was obtained that Participative Leadership, Organizational Culture, and Employee Job Satisfaction had a significant positive effect on Employee Performance. While Training had a negative and insignificant effect on Employee Performance. From the results of the moderation test, it was obtained that Employee Job Satisfaction could only moderate the relationship between Organizational Culture and Employee Performance